Altitude Research lnstitute: Looking for the solution to national problems - Alfonso-Accinelli, Roberto (2021)
The Instituto de Investigaciones de la Altura (IIA) was born 60 years ago with the creation of the Cayetano Heredia University (UPCH).It is oriented to the investigation of the adaptation and acclimatization to the altitude, and without pretending it to the solution of the national problems in health. The eradication of endemic goiter, the consolidation of the Tuberculosis Pilot Program and its expansion to a community model, the proposition that anemia in Peru is due to overdiagnosis by using an inadequate correction formula for height and a flat cut-off point for the children, knowing the beneficial effect of native plants such as maca, treatment for COVID-19 with second-indication drugs, damage to health from the use of traditional biomass stoves are some of the problems whose solutions have been born from his investigations, in addition to those found by his investigations on the problems of height.